Effect of feeding pellet containing Leucaena leucocephala and Ficus infectoria leaves on in vivo methane emission in Barbari goats - KUMAR, RAVINDRA; CHAUDHARY, U B; KUSHWAH, T (The Indian Journal of Animal Sciences, 2018)
Effect of feeding complete pellet feed containing tree leaves on methane emission was studied in male Barbari goats. Three types of complete pellet feed was formulated, viz. control pellet (C) having gram straw (60%) and concentrate mixture (40%), treatment 1 (T1) and treatment 2 (T2) containing dried Leucaena leucocephala and Ficus infectoria leaves respectively. All types of pellets were isonitrogenous. Growing male Barbari goats (12; 3– 4 month-old; average body weight 11.01±0.49 kg) were divided into 3 groups (Gr 1, Gr 2 and Gr 3) as per completely randomized design. Gr 1 was fed with control pellet while Gr 2 and Gr 3 was fed with T1 and T2 pellet respectively. After 6 weeks of experimental feeding, a digestion trial of 6-day duration was conducted. There was no difference in the DMI (g)/day between the 3 groups. Dry matter digestibility and digestibility of other nutrients were comparable among all groups of goats. Rumen liquor was collected from each animal to study rumen fermentation metabolites. Rumen pH, ammonia-N and nitrogenous fractions (total nitrogen, TCA-ppt N, NPN) were statistically similar in all the groups. Total volatile fatty acids (mmol/dl) was significantly higher in Gr 3 (10.57) and Gr 2 (9.52) as compared to control group (8.67). Fractions (%) of volatile fatty acids (acetic acid, propionic acid and butyric acid) were similar in different groups. In vivo methane emission in different groups of goats was estimated by SF6 technique as per procedure standardized in our lab. Methane production (g/day) was 8.29 in Gr 1, 7.47 in Gr 2 and 6.72 in Gr 3. There was 9.89 and 18.93% lower methane production in Gr 2 and Gr 3 as compared to control group of goats fed with complete pellet feed. From the present study, it can be concluded that incorporation of dried L. leucocephala and Ficus infectoria leaves in the complete pellet feed can reduce the methane production in goats.